Development of Ambyar Tofu Dregs Crackers Processed as an Effort to Improve the Economy of the Community of Bringinan Jambon Ponorogo Village - Tri Wulandari; Lina Fradila; Sinta Amilia; Ferry Irawan F (Jurnal Pengabdian Pancasila (JPP), 2023)
Bringinan is a village located in Jambon sub-district, Ponorogo Regency, East Java with an area of ​​138.77 ha (BPS 2021), which was formerly Bringinan Village still in the Sumoroto sub-district. Because the Sumoroto sub-district is very broad, it was divided and formed a new sub-district in Ponorogo Regency, namely Jambon. To overcome poverty, unemployment and reduce the high rate of urbanization, people are also required to be creative and innovative. One way to build a creative economy is through the home industry. The home industry is currently growing quite rapidly in Indonesia, so that the existence of a home industry can help the government in alleviating poverty and reducing unemployment. Therefore, in the aspect of the success of a village and community that has begun to be developed, there must be a new breakthrough to make a product that is later expected to become a village icon and this opportunity lies in the processing of dregs from tofu processing in Bringinan Village.